Novel chemometrics-assisted spectroscopic methods for diagnosis and monitoring of invasive ductal carcinoma in breast tissue - Albayrak, M.; Senol, O.; Demirkaya-Miloglu, F.; Calik, M.; Kadioglu, Y. (Comenius Univ, 2019)
OBJECTIVES: Early diagnosis of breast cancer is extremely important because it is the most common female cancer and a leading cause of cancer death in adult women. In this study, it is aimed to create Raman mapping with developed chemometrics-assisted Raman and FT-IR spectroscopy methods for the diagnosis of invasive ductal carcinoma (IDC) in breast tissue samples. METHODS: Samples were deparaffinized and 20-micron layers of each tissue were located on a coverslip. Mapping of both healthy and cancerous tissues were performed by exposing them to Raman laser at 532 and 758 nm while excitation was recorded at wavenumbers in range of 100-4,000 cm(-1). Orthogonal partial least square (OPLS) algorithm was applied to evaluate obtained Raman spectra. Latent variable was selected to explain the whole model. RESULTS: Healthy and IDC tissues were accurately and precisely clustered with Raman mapping and obtained results were compared to those obtained by means of histopathology and FT-IR methods. It is claimed that the proposed method has a great potential in clustering and separating IDC tissues from the healthy ones. CONCLUSION: This novel, rapid, precise, easy and objective diagnosis method may be an alternative to conventional diagnostic methods for IDC in breast tissue (Fig. 5, Ref. 22). Text in PDF www.elis.sk.
Keywords: chemometrics; FT-IR spectroscopy; invasive ductal carcinoma; Raman spectroscopy; qualitative analysis